Assessment of vehicles headway during queue dissipation at signal-controlled intersection under mixed traffic - Mondal S.; Gupta A. (My University, 2025)
The present study focuses on the comprehensive analysis of vehicles headway at signalized intersections under mixed traffic stream. Data were collected at five signalized intersections from three different cities (Allahabad, Delhi and Chandigarh) of India. The discharge headway of vehicles was analysed after the onset of green signal when the initial queue dissipated through the intersection. A box-and-whisker plot was generated for discharge headway of vehicles to quantify its equitable profile. The plot delineated that headway of vehicles decreased with the initial queue dispersion. Although the differences between headway of vehicles were almost immutable after the fifth queue position, gives a saturation headway of 2.05 sec/ vehicle. The headway distribution at each queue position was also evaluated using various continuous distribution models. The Kolmogorov-Smirnov (K-S) test was performed to define the adequate distribution model. The statistical results obtained from the K-S test indicated that the discharge headway distribution at each queue position followed a log-normal distribution. Multilinear regression technique was applied to analyse and develop a model for discharge headway using green signal time and vehicle type as independent variables. The result indicated that longer green time had a significant impact on discharge headway. The outcomes of this study may be beneficial in the microsimulation model development for signalized intersections to assess their performance. © 2019 Current Science Association, Bengaluru.